Volcanic Lakes in Africa: The VOLADA_Africa 2.0 Database, and Implications for Volcanic Hazard - Rouwet, Dmitri; Németh, Karoly; Tamburello, Giancarlo; Calabrese, Sergio; Issa, (Frontiers in Earth Science, 2021)
Here we introduce the updated, interactive and open-access database for African volcanic lakes, country by country. The previous database VOLADA (VOlcanic LAke DAta Base, Rouwet et al., 2014) reported 96 volcanic lakes for Africa. This number is now revised and established at 220, converting VOLADA_Africa 2.0 in the most comprehensive resource for African volcanic lakes: 81 in Uganda, 37 in Kenya, 33 in Cameroon, 28 in Madagascar, 19 in Ethiopia, 6 in Tanzania, 2 in Rwanda, 2 in Sudan, 2 in D.R. Congo, 1 in Libya, and 9 on the minor islands around Africa. Here we present the current state-of-the-art of arguably all the African volcanic lakes that the global experts and regional research teams are aware of, and provide hints for future research directions, with a special focus on the volcanic hazard assessment. All lakes in the updated database are classified for their genetic origin and their physical and chemical characteristics, and level of study. The predominant rift-related volcanism in Africa favors basaltic eruptive products, leading to volcanoes with highly permeable edifices (e.g. scoria), and hence less-developed hydrothermal systems. Basal aquifers accumulate under large volcanoes and in rift depressions providing a potential scenario for phreatomagmatic volcanism. This hypothesis, based on a morphometric analysis, conveys the predominance of maar lakes in large monogenetic fields in Africa (e.g. Uganda, Cameroon, Ethiopia), and the absence of peak- or high-activity crater lakes, generally found at arc-volcanoes. Considering the large number of maar lakes in Africa (172), within similar geotectonic settings and under similar meteoric conditions as in Cameroon, it is somewhat surprising that “only” from Lake Monoun and Lake Nyos fatally exsolving CO2 from the deep lake strata has been recorded. Explaining why other maars did not erupt in such fashion is a question that can only be answered by enhancing insights into physical limnology and fluid geochemistry of the so far poorly studied lakes. From a hazard perspective, there is an urgent need to tackle this task as a community.